An Analysis on Domestic Tourism Development Prospective in Karnali Province, Nepal - Dhakal, Aishwarya Prasad (NPRC Journal of Multidisciplinary Research, 2024)
The main thrust of this paper is to elucidate various aspects of domestic tourism in the specific context of Karnali Province in Nepal. To elucidate the complex interface between tourism and people, attempt have been made to provide an analysis covering various aspects related to domestic tourism policies, programs, prospects and problems. This research was conducted under Mixed Method research design because the study was described systematically the major problems and prospects of tourism development in the study area. The districts and places for domestic tourism importance have been purposively selected in order to collect valid and reliable data from the local level. Tourism is a complex process related to the work and life of people who live in the tourism potential areas. The tourism phenomenon has to make a perfect match in order to harness the benefits of tourism related activities. This research based article covers various facts of tourism development related phenomena and processes as social, cultural, religious, and natural aspects when come together make a complex form of an integrated rural network.